ZAKAT PRODUKTIF SEBAGAI MODAL USAHA MASYARAKAT (STUDI BADAN AMIL ZAKAT KOTA BENGKULU) - Dwi Putra Jaya; Hurairah Hurairah (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: The purpose of this research is clarity which can make it easy for Mustahiq (beneficiaries) to find business capital by borrowing capital at BAZNAS (The National Zakat Board) of Bengkulu City and the results of this study can be used as material for further study to produce legislation regarding the rights of Mustahiq in existing regulations. It is field research using qualitative descriptive methods. Descriptive research is to analyze the data that the author has obtained, the author uses a comparative analysis method, namely research that aims to systematically, factually, and accurately compare facts, situations or events in the field. From the results of research on the effectiveness of zakat funds received by the community, a total of eight asnaf (a Muslim person who is entitled to receive zakat and fitrah) received professional zakat assistance, those who are, fakir (a Muslim person who (a) has no property or income; or (b) has property or income but does not reach fifty per cent of the kifayah limit of himself and his dependants), poor, fisabilillah (the struggle, efforts and activities for the purpose of upholding and propagating the religion of Islam), mu'allaf (a call for individuals who are non-Muslims or non-Muslims who have the hope of converting to Islam or those who are new to Islam whose faith still needs to be supported and reinforced), and musafir (traveler), as well as productive zakat for small traders in advancing their business. The distribution of productive zakat given by BAZNAS of Bengkulu City through the